Pemberdayaan Lahan Pekarangan Masyarakat Di Desa Kelambir V Kebon - Devi Andriani Luta; Fariz Harindra Syam; Warisman Warisman (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Community housing in Klambir Lima gardens Village on average has a yard. Most of the community's yards have not been utilized as a planting area for various agricultural commodities. Besides being able to meet the needs of their own family, they also have the opportunity to increase household income sources. The method used in this activity is carried out in 3 stages, namely the initial stage is the initial survey method, socialization is carried out with a direct approach to the community (persuasive approach) in the form of deliberation, discussion, question and answer and holding counseling directions about service activities that will be carried out and the next method is practice demonstration. Community service activities carried out are expected to provide benefits to the community by empowering community yards. The benefits felt by the surrounding community are that the community can cultivate agricultural crops in their yards, the community gets information related to how to cultivate plants.